50 fantastic things to do with mud and clay - Horvath, Judit (London : Featherstone, 2017)
Cover -- Title -- Copyright -- Contents -- Introduction -- Physical development -- Mud puddle race -- Find your own clay -- Spaghetti and clay buildings -- Mudhill climbing -- Waterfalls and muddy channels -- Clay textures -- Barefoot walk -- Soil skittles -- Personal, social and emotional development -- Mud masks -- Body paint -- My body prints -- My furry friend -- Number plate for my house -- My soil -- Clay stick family -- Communication and language -- Mud café -- Make a small pond -- Magical mud -- Texture test -- Edible mud -- Mathematics -- Clay tiles -- Small world soil maze -- Underground plumbing -- Making mini bricks -- Make a soil castle -- Pattern hunt -- Soil weighing -- Clay numbers -- Literacy -- Garden signs -- Follow the trail -- Animal mark making -- Mud notes -- Secret messages from fairies -- Soil stamping -- D is for dirt -- Expressive arts and design -- Soil colour mixing -- Clay beads necklace -- Mud bakery -- Mosaic art with clay -- Dinosaur mini world -- Clay windchimes -- Splash art -- Understanding the world -- Creepy crawlies -- Minibeast chases -- Tree spirits -- Soil collecting trip -- Clay nest making -- Sensory mudbath -- Soil treasure hunt -- Mud-history
Keywords: Early childhood education -- Activity programs; Role playing in children -- Activity programs. -- Study and teaching (Early childhood); Clay -- EDUCATION / Elementary